Energy Policy in Cyprus: Outlook and Major Challenges - Zachariadis, Theodoros (My University, 2007)
This paper outlines major energy policy challenges that Cyprus is faced with. Main issues are securing the island’s energy supply and limiting growth in greenhouse gas emissions. Results from econometric analyses show that energy use is income elastic and price inelastic, which indicates that energy consumption may continue to grow rapidly in the future in the absence of appropriate price signals and energy conservation measures. Based on these results, the paper argues that policymakers need to focus on three major topics: improving energy efficiency in buildings, controlling the growth of energy use in transport, and diversifying the power generation mix. Current progress is mixed: Although energy efficiency subsidies are useful, official estimates of energy savings achieved are optimistic, and a careful assessment is necessary. In transport, the introduction of reliable public transportation systems is an urgent priority. Plans to diversify the mix of power generation are well under way regarding the introduction of natural gas, but there are delays in the introduction of renewable sources, which also limit the degree of energy market liberalisation.
Keywords: Elasticities; Transportation; Renewable energy; Conservation; Greenhouse gases.